2019
DOI: 10.1093/jnen/nlz008
|View full text |Cite
|
Sign up to set email alerts
|

Axotomy Induces Phasic Alterations in Luman/CREB3 Expression and Nuclear Localization in Injured and Contralateral Uninjured Sensory Neurons: Correlation With Intrinsic Axon Growth Capacity

Abstract: Luman/CREB3 is an important early retrograde axotomy signal regulating acute axon outgrowth in sensory neurons through the adaptive unfolded protein response. As the injury response is transcriptionally multiphasic, a spatiotemporal analysis of Luman/ CREB3 localization in rat dorsal root ganglion (DRG) with unilateral L4-L6 spinal nerve injury was conducted to determine if Luman/CREB3 expression was similarly regulated. Biphasic alterations in Luman/CREB3 immunofluorescence and nuclear localization occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 73 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…In dorsal root ganglion sensory neurons CREB3 localizes to the soma and the axonal ER. In response to nerve injury, CREB3 is synthesized in axons and transported to the nuclei of injured neurons via importin-dependent retrograde transport (Hasmatali et al, 2019). Interestingly, immunoprecipitation assays indicated that CREB3 interacts with importin, but CREB3-target genes involved in axon growth were not identified.…”
Section: Creb3 Family In the Central Nervous Systemmentioning
confidence: 99%
“…In dorsal root ganglion sensory neurons CREB3 localizes to the soma and the axonal ER. In response to nerve injury, CREB3 is synthesized in axons and transported to the nuclei of injured neurons via importin-dependent retrograde transport (Hasmatali et al, 2019). Interestingly, immunoprecipitation assays indicated that CREB3 interacts with importin, but CREB3-target genes involved in axon growth were not identified.…”
Section: Creb3 Family In the Central Nervous Systemmentioning
confidence: 99%
“…It should be noted that in our experiments, we have performed a unilateral conditioning lesion and then compared the effects in the ipsilateral to those in the contralateral DRGs. This comparison may underestimate the magnitude of the effect on the ipsilateral ganglia, as in recent studies in the rat, it has been shown that, after spinal nerve transection, some stimulation of gene expression and neurite outgrowth occurs not only in the ipsilateral DRGs but also, though to a lesser extent, in the contralateral DRGs (Hasmatali et al, 2019;Hasmatali et al, 2020;Verge et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Notably, CREB3 synthesis and releasing from the axonal endoplasmic reticulum was induced by axotomy and then transferred to the cell nucleus in an importin-mediated manner [ 39 ], which regulates the unfolded protein response (UPR ER ) and cholesterol biosynthesis that are crucially associating with the acute stress response in axonal growth [ 39 , 40 ]. The authors also show that upregulation and nuclear localization of Luman coordinate with the increased transcriptional activity in injured neurons, achieving maximal outgrowth capacity at two-day injury-conditioned neurons relative to naïve [ 41 ].…”
Section: Injury Signal Transduction Of the Preconditioning Injury mentioning
confidence: 99%